A referenciação e a construção de sentido(s) no texto digital: um olhar fenomenológico - CARDOSO, Evaldo Carlos De Oliveira (2019)
The reference consists of a discursive practice in which the construction of referents, objects of discourse, happens in a negotiated way, in a conception of language as a sociocognitive activity. In this sense, the socio-cultural interactions and the context begin to interfere directly in the referential process. The present work aims to investigate, under the socio-cognitive-interactionist and discursive perspective, the process of reference and the construction of meaning (s) in the digital text, based on the analysis of linguistic realizations of interacting subjects on Facebook. As a theoretical contribution, we used the studies of authors such as Cavalcante (2011, 2012, 2013, 2014, 2017), Crystal (2001), Barton e Lee (2015), Koch (2010, 2012, 2015, 2017), Lévy (2010, 2011), Marcuschi (2008, 2010, 2012, 2017), Mondada (1994, 1995, 2017), Mondada e Dubois (2016), Recuero (2014), Shepherd e Saliés (2013), among others who discuss the referential question, the Internet language and the digital text, enabling the unveiling of the phenomenon under our investigation. The methodological procedures are based on the Hermeneutic Phenomenology of Paul Ricoeur (1989, 1991, 1996, 2005) and, for the collection of data, we chose to construct a corpus composed of texts/comments captured from a page created within the social network Facebook, Debate News, exclusively for this research. For the analysis of the data, we are guided by the following guiding question: How is the process of reference in the digital text carried out? Among the texts/comments of the constructed corpus, only 4 (four) were selected for analysis. The results allowed us to answer the guiding question of our research, helping us to understand how the process of reference is carried out in the digital text, leading us to affirm that this process is carried out based on what the subjects mean, that is, of the construction of meaning(s) that becomes effective in their discursive practices, within a dynamic interaction environment – the social network Facebook –, which occurs in a process of negotiation, cooperation and shared subjectivity.